Transcription factor modularity in a gene-centered C. elegans core neuronal protein–DNA interaction network - Vermeirssen, Vanessa; Barrasa, M. Inmaculada; Hidalgo, César A.; Babon, Jenny Aurielle B.; Sequerra, Reynaldo; Doucette-Stamm, Lynn; Barabási, Albert-László; Walhout, Albertha J.M. (Genome Research, 2007)
Transcription regulatory networks play a pivotal role in the development, function, and pathology of metazoan organisms. Such networks are comprised of protein–DNA interactions between transcription factors (TFs) and their target genes. An important question pertains to how the architecture of such networks relates to network functionality. Here, we show that a Caenorhabditis elegans core neuronal protein–DNA interaction network is organized into two TF modules. These modules contain TFs that bind to a relatively small number of target genes and are more systems specific than the TF hubs that connect the modules. Each module relates to different functional aspects of the network. One module contains TFs involved in reproduction and target genes that are expressed in neurons as well as in other tissues. The second module is enriched for paired homeodomain TFs and connects to target genes that are often exclusively neuronal. We find that paired homeodomain TFs are specifically expressed in C. elegans and mouse neurons, indicating that the neuronal function of paired homeodomains is evolutionarily conserved. Taken together, we show that a core neuronal C. elegans protein–DNA interaction network possesses TF modules that relate to different functional aspects of the complete network.
10.1101/gr.6148107